Resin composition as well as preparation method and application thereof
Through the use of modified epoxy resin composition, the problem of insufficient performance of traditional resin composition in high voltage and high current environments is solved, rapid curing without baking and efficient automated production is achieved, and product life and performance are improved. In the manufacturing of new energy power batteries and automotive high-voltage thick film flexible wiring harnesses, it meets the requirements of low-carbon green manufacturing.
Patent Information
- Application Number
- CN202411474144.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2025-01-03
AI Technical Summary
The existing FPC flexible copper clad technology cannot meet the high voltage and high current requirements of new energy power batteries and automobile high-voltage thick film flexible wire harnesses. The traditional resin composition has poor peeling strength, long curing time and high energy consumption after the wire thickness increases. Moreover, the storage life is short, making it difficult to adapt to roll-to-roll and large-size wire harness manufacturing, and does not conform to the development concept of low-carbon green manufacturing.
A modified epoxy resin composition has been developed, which has the characteristics of baking and fast curing, and is used for the production of cover films, which can provide sufficient adhesion, support automated roll-to-roll rolling process, and is suitable for large cross sections. Preparation of copper wire covering films with area, including modified epoxy resin, epoxy resin, phenolic resin, curing agent, accelerator, flame retardant and coupling agent, and build an interpenetrating network through specific grafting reactions and molecular weight control. Structure to improve adhesion and heat resistance.
It significantly improves the storage life of the product, realizes continuous production of circuit boards, meets the needs of high power, low energy consumption and low cost, has excellent flame retardant performance, peel strength and chemical corrosion resistance, and is suitable for new energy power batteries. The automated production of high-pressure thick film flexible wiring harnesses in automobiles has promoted the technological upgrading and sustainable development of related industries.
Smart Images

Figure CN119241987A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of circuit board preparation, and specifically relates to a resin composition and a preparation method and application thereof. Background Art
[0002] FPC (Flexible Printed Circuit, flexible plastic circuit board, referred to as FPC) is a basic material used to manufacture flexible circuit boards. It consists of a flexible substrate (usually polyimide or polyester) and a layer of copper foil coated on its surface or copper wire laid. The structure is as follows Figure 1 As shown. Due to the increasing demand for high voltage and high current in new energy power battery pack wiring harnesses and automotive high-voltage thick film flexible wiring harnesses, the existing FPC flexible copper clad laminate process is no longer competent. To this end, the latest design structure introduces copper wires with larger cross-sectional areas to meet the high voltage and high current requirements, and realizes the manufacturing of thick film copper wire flexible wiring harnesses through the covering film rapid pressing technology.
[0003] Circuit graphics or wiring harness products produced by traditional subtractive etching technology will be gradually eliminated because they cannot meet the needs of subsequent technological development. Flexible printed circuit boards are widely used in the field of electronic products because of their light, thin, short and small characteristics. However, in the context of new energy power batteries pursuing endurance and high power output, the original etching circuit process can no longer meet the requirements of high voltage and high current. As one of the iterative technical solutions, copper wire conductors with larger cross-sectional areas are introduced. However, this change also brings new challenges. The existing resin compositions and covering films cannot meet the technical requirements after the thickness of the wires increases. Specifically, they are manifested in poor peel strength, long curing time, high energy consumption, and difficulty in supporting roll-to-roll and larger size wiring harness manufacturing. In addition, these materials have a short storage life, which increases supply chain costs and does not conform to the development concept of low-carbon and green manufacturing.
[0004] Cover film is a film-like insulating material coated with adhesive on one side of an insulating base film such as polyimide film or polyester film. As a key component of a flexible printed circuit board, it covers the surface of the circuit and not only acts as a solder mask, effectively protecting the circuit from dust, moisture, chemical corrosion and other forms of damage, but also has an enhancement function, improving the flexural resistance of the flexible printed circuit board. Traditionally, cover films mainly use epoxy adhesives and acrylic adhesives. Both adhesives need to be applied under fast pressure or pressure transfer conditions to achieve effective bonding and circuit filling effects, and need to undergo a baking process at 160°C for 2 to 3 hours to ensure that the curing reaction of the adhesive is completed, thereby generating the required bonding force.
[0005] However, the current shelf life of covering film products under refrigerated conditions (5℃±3℃) is only 3 months at most, and the performance data will show a significant decline within 1 month from the production date. This phenomenon has brought many inconveniences to the supply chain, invisibly increased the supply chain cost and the risk of material scrapping, and also had an adverse impact on the quality stability of downstream products. More importantly, the traditional long-term baking curing method is difficult to meet the production needs of roll-to-roll rolling. The sheet pressing method is not only inefficient, but also cannot adapt to the production of large-size flexible printed circuit boards, and it is even more difficult to meet the production needs of thick-film copper wire lines / wiring harnesses with larger cross-sectional areas. At present, the performance of the covering film adhesive layer has become a key factor restricting the manufacturing of new products. It is impossible to achieve a more efficient, low-energy, green and low-carbon production concept, and it is not in line with the development direction of new energy power batteries and automotive high-power wiring harness technology.
[0006] Therefore, it is necessary to develop a new material that can implement a roll-to-roll rolling process and is suitable for the preparation of copper wire covering films with large cross-sectional areas to meet the needs of new energy power battery packs and automotive high-voltage thick-film flexible wiring harnesses. Summary of the invention
[0007] The present invention aims to solve at least one of the above-mentioned technical problems existing in the prior art. To this end, the present invention provides a resin composition, which has the characteristics of no baking and fast curing, can be directly applied to the production of covering film, can provide sufficient bonding force, and can be directly used for the bonding of large-diameter copper wires or thick copper foils in circuit boards. And it only takes about 160 seconds to complete hot pressing by rollers, realizing the continuous production of circuit boards. Not only does it significantly improve the storage life of the product, but it also has vital strategic significance for promoting the development of new energy power battery packs and automotive high-voltage thick film flexible wiring harnesses towards higher power, higher efficiency, lower energy consumption and lower cost.
[0008] The invention also provides a method for preparing the resin composition.
[0009] The invention also provides a covering film.
[0010] The invention also provides a method for preparing the covering film.
[0011] The first aspect of the present invention provides a resin composition, the raw materials for preparing the resin composition include: modified epoxy resin, epoxy resin, phenolic resin, curing agent, accelerator, flame retardant and coupling agent, wherein the modified epoxy resin is a rubber graft reaction polymer.
[0012] One of the technical solutions of the present invention regarding the resin composition has at least the following beneficial effects:
[0013] In order to meet the high voltage and high current requirements in the wiring harness of new energy power battery packs and the high-voltage thick film flexible wiring harness of automobiles, copper wires with larger cross-sectional areas are introduced in the design of the circuit board. In the traditional circuit board preparation process, PI film and PET film both need glue bonding, the cover film can only be pressed with a thickness of about 7 microns, and the etching method of the traditional process needs to discharge waste. In addition to the problems in pressing, the traditional preparation method also requires high-temperature baking, and the length of the circuit board can reach more than 2 meters, which requires segmented preparation and cannot achieve continuous production. The resin composition of the present invention has the characteristics of free baking and rapid curing, can be directly applied to the production of the cover film, can provide sufficient bonding force, and can be directly used for the bonding of large-diameter copper wires or thick copper foils in the circuit board. And it only takes about 160s to complete the hot pressing by the roller, realizing the continuous production of the circuit board. Not only does it significantly improve the storage life of the product, but it also has vital strategic significance for promoting the development of new energy power battery packs and automotive high-voltage thick film flexible wiring harnesses towards higher power, higher efficiency, lower energy consumption and lower cost.
[0014] The core goal of the present invention is to develop a resin composition that significantly improves the storage life of the covering film in a refrigerated environment. This composition can not only prepare a material with halogen-free flame retardant properties without baking, but also has a flame retardant grade of V-0, which meets the industry standard, demonstrating excellent flame retardant performance. In addition, the material also exhibits excellent peel strength, chemical corrosion resistance and thermal stability, ensuring its reliable application in complex environments.
[0015] More importantly, the resin composition supports the automated roll-to-roll rolling process, providing strong technical support for the automated production of new energy power battery packs and automotive high-voltage thick-film copper wire flexible wiring harnesses. The present invention not only meets the market's urgent demand for higher power, higher efficiency, and lower energy consumption, but also actively responds to the green and low-carbon development concept. It is particularly suitable for the manufacture of large-size high-voltage thick-film copper wire flexible circuits and wiring harnesses, and promotes the technological upgrading and sustainable development of related industries.
[0016] In the resin composition of the present invention, modified epoxy resin, as the core matrix resin, significantly improves the flexibility and bonding strength of the resin composition. Through specific modification means, epoxy resin can more effectively construct an interpenetrating network structure, thereby strengthening adhesion and cohesion. In addition, the epoxy resin and phenolic resin components incorporated in the composition jointly enhance the crosslinking density of the system, giving the resin composition excellent heat resistance and adjustable overflow characteristics. It should be noted that thermoplastic phenolic resin, due to its excellent high temperature fluidity, not only improves the overall fluidity and heat resistance of the resin composition, but also significantly improves the insulation resistance capacity, ensuring that the prepared cover film can show excellent line filling performance, bonding strength and high insulation resistance characteristics under the rolling processing environment.
[0017] In the resin composition of the present invention:
[0018] Modified epoxy resin is used as the core matrix to enhance the flexibility and bonding strength of the resin, promote the formation of an interpenetrating network structure, and improve the overall performance.
[0019] Epoxy resins enhance the crosslink density of the system, provide excellent mechanical strength and thermal stability, and help improve adhesion.
[0020] Phenolic resin provides good heat resistance and fluidity, improving overall insulation performance and chemical corrosion resistance.
[0021] Curing agents cause the resin to cure under heat or catalysis, forming a strong network structure and ensuring the durability of the final material.
[0022] Accelerators speed up the curing reaction, improve production efficiency and shorten the curing time.
[0023] The flame retardant gives the material halogen-free flame retardant properties, ensuring safety in the event of a fire and achieving V-0 level flame retardant properties.
[0024] Coupling agents improve the bonding between the resin and filler or substrate, enhancing the adhesion and stability of the material.
[0025] The synergistic effect of these ingredients enables the resin composition to perform well in high-performance applications.
[0026] According to some embodiments of the present invention, the raw materials for preparation include, by weight: modified epoxy resin: 100 parts,
[0027] Epoxy resin: 10-20 parts,
[0028] Phenolic resin: 10-20 parts,
[0029] Curing agent: 5-15 parts,
[0030] Accelerator: 2-10 parts,
[0031] Flame retardant: 40-60 parts,
[0032] Coupling agent: 0.1-0.5 parts.
[0033] According to some embodiments of the present invention, the preparation method of the modified epoxy resin is: performing a grafting reaction on carboxyl-terminated butyl rubber and EBA23 epoxy resin at 150°C.
[0034] According to some embodiments of the present invention, the polymerization degree of the modified epoxy resin is 50% to 55%.
[0035] According to some embodiments of the present invention, the number average molecular weight of the modified epoxy resin is 4,000 to 10,000.
[0036] The molecular weight control during the modified epoxy resin grafting reaction process is the core element to ensure the subsequent adhesion and flow filling performance. If the molecular weight is set too low, it will cause the problem of insufficient colloid cohesion; on the contrary, too high a molecular weight will lead to a weakened reaction activity, thereby prolonging the reaction time. Specifically, the number average molecular weight of the modified epoxy resin after grafting should be maintained in the range of 4000 to 10000, such as any value between 4000, 4500, 5000, 5500, 7500, 8000, 8500 and 10000 or a range formed by any two of them, such as 5000 to 7500.
[0037] Within the framework of the present invention, if the molecular weight of the modified epoxy resin is lower than the lower limit of this range, it will lead to insufficient molding performance and bonding strength, thereby weakening the peel strength and cohesion; if its molecular weight exceeds the upper limit of this range, it will reduce the fluidity of the resin composition, causing the glue modulus to increase abnormally after lamination, reducing the filling performance, and may have an adverse effect on the peel strength and heat resistance.
[0038] The number average molecular weight is determined by gel permeation chromatography based on polyvinyl chloride calibration in accordance with GB / T21863-2008.
[0039] According to some embodiments of the present invention, the epoxy resin is a bifunctional epoxy resin or a multifunctional epoxy resin.
[0040] According to some embodiments of the present invention, the epoxy value of the epoxy resin is 0.18 to 1.02 mol / 100 gr.
[0041] According to some embodiments of the present invention, the epoxy resin includes at least one of bisphenol A epoxy resin, bisphenol F epoxy resin, linear novolac epoxy resin, naphthyl epoxy resin and biphenyl epoxy resin.
[0042] According to some embodiments of the present invention, the phenolic resin is a thermoplastic novolac resin.
[0043] Thermoplastic phenolic resin has a softening point of 85℃-95℃ and has good high-temperature fluidity, which gives the resin composition good fluidity, excellent heat resistance, and adjustable overflow. The crosslinking density can also be adjusted in the resin composition, achieving excellent circuit filling and heat resistance.
[0044] According to some embodiments of the present invention, the curing agent includes at least one of an aromatic amine curing agent, an amine-modified curing agent, an acid anhydride curing agent, an imidazole curing agent and a latent curing agent.
[0045] According to some embodiments of the present invention, the curing agent includes at least one of 4,4'-diaminodiphenyl sulfone, 3,3'-diaminodiphenyl sulfone, DDS, hydrazide, methyl nadic anhydride, phthalic anhydride, tetrahydrophthalic anhydride, PN-23, PN-23J, PN-40, PN-40J and 2EMI.
[0046] According to some embodiments of the present invention, the accelerator includes at least one of a modified amine accelerator, an imidazole accelerator, an organic urea accelerator and a hydrazide accelerator.
[0047] According to some embodiments of the present invention, the accelerator includes at least one of N,N'-diethyldiphenylurea, 1,1,3,3-tetramethylurea, PN-23, PN-23, PN-23J, PN-40, PN-40J, and 2EMI.
[0048] According to some embodiments of the invention, the flame retardant comprises a phosphorus-containing flame retardant.
[0049] According to some embodiments of the present invention, the flame retardant may be a compound of aluminum hydroxide and a phosphorus-containing flame retardant in a weight ratio of 1:3.
[0050] According to some embodiments of the present invention, the coupling agent includes a silane coupling agent.
[0051] According to some embodiments of the present invention, based on 100 parts of the modified epoxy resin, the amount of the coupling agent added is 0.1 to 0.5 parts, specifically any value among 0.1, 0.2, 0.3, 0.4, 0.5 or a range formed by any two of them.
[0052] The second aspect of the present invention provides a method for preparing the resin composition of the first aspect of the present invention, comprising the following steps: dispersing and mixing the modified epoxy resin, the epoxy resin, the phenolic resin, the curing agent, the accelerator, the flame retardant and the coupling agent in an organic solvent according to a proportion.
[0053] A technical solution in the method for preparing a resin composition of the present invention has at least the following beneficial effects:
[0054] By dispersing and mixing the organic solvent, uniform distribution of each component can be achieved, thereby improving the overall performance of the resin composition.
[0055] This method simplifies the traditional process flow and reduces the need for high-temperature baking, making the production process more efficient and environmentally friendly. In addition, good dispersibility helps to improve the bonding strength and heat stability of the final material, ensuring its reliability in complex environments. Ultimately, this method not only meets the market demand for high-performance materials, but also promotes technological progress in related industries.
[0056] According to some embodiments of the present invention, the organic solvent includes at least one of acetone, butanone, cyclohexanone, ethylene glycol monomethyl ether, propylene glycol methyl ether acetate, ethyl acetate, butyl acetate and DMF.
[0057] A third aspect of the present invention provides a cover film, comprising an insulating base film and an adhesive layer coated on the insulating base film, wherein the adhesive layer is formed from the resin composition of the first aspect of the present invention.
[0058] The technical solution of the covering film of the present invention has at least the following beneficial effects:
[0059] The resin composition of the present invention enables the covering film to have a storage life of 6 months under refrigeration, and can be made to have halogen-free flame retardancy in a baking-free state, and the flame retardancy grade can reach V-0 level, with good peel strength, chemical resistance and heat resistance, and can realize automatic roll-to-roll rolling, reduce process energy consumption, improve process efficiency, reduce manufacturing costs, meet the requirements of low-carbon green environmental protection, and can better meet the automatic processing and performance indicators of new energy power battery wiring harnesses and automotive high-power thick film copper wire harnesses. It meets the technical requirements of high voltage and high current; it meets the peel strength, heat resistance, chemical resistance, halogen-free, flame retardancy grade V-0 of thick film copper wire harnesses, and roll-to-roll rolling can efficiently produce thick film copper wire harnesses.
[0060] The excellent heat resistance and peel strength of the cover film enable it to maintain stable performance in high temperature and high current environments, ensuring the reliability of electrical insulation and connection. In addition, the halogen-free flame retardancy of the adhesive layer not only meets safety standards, but also reduces the negative impact on the environment, in line with the concept of green environmental protection. The film's automated roll-to-roll processing characteristics can significantly improve production efficiency, reduce labor costs, and adapt to large-scale production needs.
[0061] According to some embodiments of the present invention, the insulating base film is at least one of a polyimide film, a polyethylene film, a polypropylene film, a polyethylene terephthalate film, and a PET film.
[0062] The fourth aspect of the present invention provides a method for preparing the covering film according to the third aspect of the present invention, comprising the following steps:
[0063] The resin composition is mixed and dispersed in an organic solvent to obtain a resin glue solution, which is then applied to the insulating base film and heated for curing.
[0064] The technical solution of the method for preparing the covering film of the present invention has at least the following beneficial effects:
[0065] First, by mixing and dispersing in an organic solvent, the uniformity of the resin glue can be achieved, ensuring the performance consistency of the covering film. Secondly, the process of heating and curing after coating increases the degree of cross-linking of the resin, thereby enhancing the strength, heat resistance and chemical stability of the film. In addition, this method simplifies the production process, reduces energy consumption and costs, meets the requirements of green manufacturing, and is particularly suitable for large-scale automated production.
[0066] According to some embodiments of the present invention, the method for preparing the covering film may be:
[0067] The modified epoxy resin was prepared using a three-mouth glass reactor, that is, carboxyl-terminated butyl rubber and EBA23 epoxy resin were grafted at 150°C.
[0068] Furthermore, the other components of the resin composition are mixed with an organic solvent, and a ball mill, a jar mill, a sand mill or the like is used in combination with a high shear stirring and dispersing device to mix the organic solid components in the resin composition and the added inorganic solid components with the organic solvent to prepare a resin composition glue.
[0069] Furthermore, the resin composition glue is coated on an insulating substrate using a coating device; the insulating substrate coated with the resin composition glue is then heated at 80 to 160° C. for 2 to 10 minutes in an online drying oven; the organic solvent is removed and the covering film is obtained by winding. BRIEF DESCRIPTION OF THE DRAWINGS
[0070] Figure 1 It is a structural diagram of the FPC board. DETAILED DESCRIPTION
[0071] The following are specific embodiments of the present invention, and the technical solutions of the present invention are further described in conjunction with the embodiments, but the present invention is not limited to these embodiments.
[0072] In the first aspect, some embodiments of the present invention provide a resin composition, wherein the raw materials for preparing the resin include: modified epoxy resin, epoxy resin, phenolic resin, curing agent, accelerator, flame retardant and coupling agent, wherein the modified epoxy resin is a rubber grafted reaction polymer.
[0073] It can be understood that in order to meet the high voltage and high current requirements in the wiring harness of new energy power battery packs and the high-voltage thick film flexible wiring harness of automobiles, copper wires with larger cross-sectional areas are introduced in the design of the circuit board. In the traditional circuit board preparation process, PI film and PET film both need glue bonding, the cover film can only be pressed with a thickness of about 7 microns, and the etching method of the traditional process needs to discharge waste. In addition to the problems in pressing, the traditional preparation method also requires high-temperature baking, and the length of the circuit board can reach more than 2 meters, which requires segmented preparation and cannot achieve continuous production. The resin composition of the present invention has the characteristics of free baking and rapid curing, can be directly applied to the production of the cover film, can provide sufficient bonding force, and can be directly used for the bonding of large diameter copper wires or thick copper foils in the circuit board. And it only takes about 160s to complete the hot pressing by the roller, realizing the continuous production of the circuit board. Not only does it significantly improve the storage life of the product, but it also has vital strategic significance for promoting the development of new energy power battery packs and automotive high-voltage thick film flexible wiring harnesses towards higher power, higher efficiency, lower energy consumption and lower cost.
[0074] The core goal of the present invention is to develop a resin composition that significantly improves the storage life of the covering film in a refrigerated environment. This composition can not only prepare a material with halogen-free flame retardant properties without baking, but also has a flame retardant grade of V-0, which meets the industry standard, demonstrating excellent flame retardant performance. In addition, the material also exhibits excellent peel strength, chemical corrosion resistance and thermal stability, ensuring its reliable application in complex environments.
[0075] More importantly, the resin composition supports the automated roll-to-roll rolling process, providing strong technical support for the automated production of new energy power battery packs and automotive high-voltage thick-film copper wire flexible wiring harnesses. The present invention not only meets the market's urgent demand for higher power, higher efficiency, and lower energy consumption, but also actively responds to the green and low-carbon development concept. It is particularly suitable for the manufacture of large-size high-voltage thick-film copper wire flexible circuits and wiring harnesses, and promotes the technological upgrading and sustainable development of related industries.
[0076] In the resin composition of the present invention, modified epoxy resin, as the core matrix resin, significantly improves the flexibility and bonding strength of the resin composition. Through specific modification means, epoxy resin can more effectively construct an interpenetrating network structure, thereby strengthening adhesion and cohesion. In addition, the epoxy resin and phenolic resin components incorporated in the composition jointly enhance the crosslinking density of the system, giving the resin composition excellent heat resistance and adjustable overflow characteristics. It should be noted that thermoplastic phenolic resin, due to its excellent high temperature fluidity, not only improves the overall fluidity and heat resistance of the resin composition, but also significantly improves the insulation resistance capacity, ensuring that the prepared cover film can show excellent line filling performance, bonding strength and high insulation resistance characteristics under the rolling processing environment.
[0077] In combination with the first aspect, in some embodiments of the present invention, the raw materials for preparation include, by weight: modified epoxy resin: 100 parts,
[0078] Epoxy resin: 10-20 parts,
[0079] Phenolic resin: 10-20 parts,
[0080] Curing agent: 5-15 parts,
[0081] Accelerator: 2-10 parts,
[0082] Flame retardant: 40-60 parts,
[0083] Coupling agent: 0.1-0.5 parts.
[0084] In combination with the first aspect, in some embodiments of the present invention, the preparation method of the modified epoxy resin is: grafting the carboxyl-terminated butyl rubber and EBA23 epoxy resin at 150°C.
[0085] In combination with the first aspect, in some embodiments of the present invention, the polymerization degree of the modified epoxy resin is 50% to 55%.
[0086] In combination with the first aspect, in some embodiments of the present invention, the number average molecular weight of the modified epoxy resin is 4,000 to 10,000.
[0087] The molecular weight control during the modified epoxy resin grafting reaction process is the core element to ensure the subsequent adhesion and flow filling performance. If the molecular weight is set too low, it will cause the problem of insufficient colloid cohesion; on the contrary, too high a molecular weight will lead to a weakened reaction activity, thereby prolonging the reaction time. Specifically, the number average molecular weight of the modified epoxy resin after grafting should be maintained in the range of 4000 to 10000, such as any value between 4000, 4500, 5000, 5500, 7500, 8500 and 10000 or a range formed by any two values, such as 5000 to 7500.
[0088] Within the framework of the present invention, if the molecular weight of the modified epoxy resin is lower than the lower limit of this range, it will lead to insufficient molding performance and bonding strength, thereby weakening the peel strength and cohesion; if its molecular weight exceeds the upper limit of this range, it will reduce the fluidity of the resin composition, causing the glue modulus to increase abnormally after lamination, reducing the filling performance, and may have an adverse effect on the peel strength and heat resistance.
[0089] The number average molecular weight is determined by gel permeation chromatography based on polyvinyl chloride calibration in accordance with GB / T21863-2008.
[0090] In combination with the first aspect, in some embodiments of the present invention, the epoxy resin is a difunctional epoxy resin or a multifunctional epoxy resin.
[0091] In combination with the first aspect, in some embodiments of the present invention, the epoxy value of the epoxy resin is 0.18 to 1.02 mol / 100 gr.
[0092] In combination with the first aspect, in some embodiments of the present invention, the epoxy resin includes at least one of bisphenol A epoxy resin, bisphenol F epoxy resin, linear novolac epoxy resin, naphthyl epoxy resin and biphenyl epoxy resin.
[0093] In combination with the first aspect, in some embodiments of the present invention, the phenolic resin is a thermoplastic phenolic resin.
[0094] Thermoplastic phenolic resin has a softening point of 85℃-95℃ and has good high-temperature fluidity, which gives the resin composition good fluidity, excellent heat resistance, and adjustable overflow. The crosslinking density can also be adjusted in the resin composition, achieving excellent circuit filling and heat resistance.
[0095] In combination with the first aspect, in some embodiments of the present invention, the curing agent includes at least one of an aromatic amine curing agent, an amine-modified curing agent, an acid anhydride curing agent, an imidazole curing agent and a latent curing agent.
[0096] In combination with the first aspect, in some embodiments of the present invention, the curing agent includes at least one of 4,4'-diaminodiphenyl sulfone, 3,3'-diaminodiphenyl sulfone, DDS, hydrazide, methyl nadic anhydride, phthalic anhydride, tetrahydrophthalic anhydride, PN-23, PN-23J, PN-40, PN-40J and 2EMI.
[0097] In combination with the first aspect, in some embodiments of the present invention, the accelerator includes at least one of a modified amine accelerator, an imidazole accelerator, an organic urea accelerator and a hydrazide accelerator.
[0098] In combination with the first aspect, in some embodiments of the present invention, the accelerator includes at least one of N,N'-diethyldiphenylurea, 1,1,3,3-tetramethylurea, PN-23, PN-23, PN-23J, PN-40, PN-40J, and 2EMI.
[0099] In combination with the first aspect, in some embodiments of the present invention, the flame retardant includes a phosphorus-containing flame retardant.
[0100] In combination with the first aspect, in some embodiments of the present invention, the flame retardant may be a compound of aluminum hydroxide and a phosphorus-containing flame retardant in a weight ratio of 1:3.
[0101] In combination with the first aspect, in some embodiments of the present invention, the coupling agent includes a silane coupling agent.
[0102] In combination with the first aspect, in some embodiments of the present invention, based on 100 parts of the modified epoxy resin, the amount of coupling agent added is 0.1 to 0.5 parts, specifically any value among 0.1, 0.2, 0.3, 0.4, 0.5 or a range formed by any two of them.
[0103] In the second aspect, some embodiments of the present invention provide a method for preparing the resin composition of the first aspect of the present invention, comprising the following steps: dispersing and mixing modified epoxy resin, epoxy resin, phenolic resin, curing agent, accelerator, flame retardant and coupling agent in an organic solvent according to a proportion.
[0104] It can be understood that, through the dispersion and mixing of the organic solvent, uniform distribution of the components can be achieved, thereby improving the overall performance of the resin composition.
[0105] It can also be understood that this method simplifies the traditional process flow, reduces the need for high-temperature baking, and makes the production process more efficient and environmentally friendly. In addition, good dispersibility helps to improve the bonding strength and heat resistance stability of the final material, ensuring its reliability in complex environments. Ultimately, this method not only meets the market demand for high-performance materials, but also promotes technological progress in related industries.
[0106] In combination with the second aspect, in some embodiments of the present invention, the organic solvent includes at least one of acetone, butanone, cyclohexanone, ethylene glycol monomethyl ether, propylene glycol methyl ether acetate, ethyl acetate, butyl acetate and DMF.
[0107] In a third aspect, some embodiments of the present invention provide a covering film, comprising an insulating base film and an adhesive layer coated on the insulating base film, wherein the adhesive layer is formed from the resin composition of the first aspect of the present invention.
[0108] The resin composition of the present invention enables the covering film to have a storage life of 6 months under refrigeration, and can be made to have halogen-free flame retardancy in a baking-free state, and the flame retardancy grade can reach V-0 level, with good peel strength, chemical resistance and heat resistance, and can realize automatic roll-to-roll rolling, reduce process energy consumption, improve process efficiency, reduce manufacturing costs, meet the requirements of low-carbon green environmental protection, and can better meet the automatic processing and performance indicators of new energy power battery wiring harnesses and automotive high-power thick film copper wire harnesses. It meets the technical requirements of high voltage and high current; it meets the peel strength, heat resistance, chemical resistance, halogen-free, flame retardancy grade V-0 of thick film copper wire harnesses, and roll-to-roll rolling can efficiently produce thick film copper wire harnesses.
[0109] The excellent heat resistance and peel strength of the cover film enable it to maintain stable performance in high temperature and high current environments, ensuring the reliability of electrical insulation and connection. In addition, the halogen-free flame retardancy of the adhesive layer not only meets safety standards, but also reduces the negative impact on the environment, in line with the concept of green environmental protection. The film's automated roll-to-roll processing characteristics can significantly improve production efficiency, reduce labor costs, and adapt to large-scale production needs.
[0110] In combination with the third aspect, in some embodiments of the present invention, the insulating base film is at least one of a polyimide film, a polyethylene film, a polypropylene film, a polyethylene terephthalate film, and a PET film.
[0111] In a fourth aspect, in some embodiments of the present invention, there is provided a method for preparing the covering film according to the third aspect of the present invention, comprising the following steps:
[0112] The resin composition is mixed and dispersed in an organic solvent to obtain a resin glue solution, which is then applied to an insulating base film and heated for curing.
[0113] It can be understood that, firstly, by mixing and dispersing in an organic solvent, the uniformity of the resin glue can be achieved, ensuring the performance consistency of the covering film. Secondly, the process of heating and curing after coating increases the degree of cross-linking of the resin, thereby enhancing the strength, heat resistance and chemical stability of the film. In addition, this method simplifies the production process, reduces energy consumption and costs, meets the requirements of green manufacturing, and is particularly suitable for large-scale automated production.
[0114] In conjunction with the fourth aspect, in some embodiments of the present invention, the method for preparing the covering film may be:
[0115] The modified epoxy resin was prepared using a three-mouth glass reactor, that is, carboxyl-terminated butyl rubber and EBA23 epoxy resin were grafted at 150°C.
[0116] Furthermore, the other components of the resin composition are mixed with an organic solvent, and a ball mill, a jar mill, a sand mill or the like is used in combination with a high shear stirring and dispersing device to mix the organic solid components in the resin composition and the added inorganic solid components with the organic solvent to prepare a resin composition glue.
[0117] Furthermore, the resin composition glue is coated on the insulating substrate using a coating device; the insulating substrate coated with the resin composition glue is then heated at 80 to 160° C. for 2 to 10 minutes in an online drying oven; the organic solvent is removed and the covering film is obtained by winding.
[0118] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present invention.
[0119] In the description of the present invention, the description with reference to the terms "one embodiment", "some embodiments", "illustrative embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.
[0120] Unless otherwise specified, "room temperature" in the present invention means 25°C±5°C.
[0121] Unless otherwise specified, "about" in the present invention means that the allowable error is within ±2%.
[0122] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be purchased commercially. The main reagent information is as follows:
[0123] CTBN: Japan Zeon 1072CGJ.
[0124] EBA23: Shanghai Huayi Company's EBA23, epoxy value 0.18-0.28mol / 100gr, viscosity 10000-15000cps.
[0125] NPCN-703: South Asia, softening point 75-85℃.
[0126] NPEL-134: South Asia, Liquid.
[0127] HN-7000, MTHPA: Hitachi Chemical.
[0128] DMP-30: Shanghai Luhe Hi-Tech.
[0129] DF-602: Loctite.
[0130] OP-935: Swiss CLARIANT EXOLIT.
[0131] Z-6040: Dow Corning, USA.
[0132] Example 1
[0133] A resin composition, prepared from the following raw materials:
[0134] CTBN: 30 copies,
[0135] Bisphenol A epoxy resin EBA-23: 70 parts,
[0136] Bisphenol A epoxy resin NPEL-134: 17 parts,
[0137] Phenolic resin PF-2123: 13 parts,
[0138] Anhydride curing agent HN-7000: 9 parts,
[0139] Accelerator DMP-30: 4.8 parts,
[0140] Flame retardant OP-935: 50 parts,
[0141] Coupling agent Z-6040: 0.2 parts.
[0142] The number average molecular weight of the modified epoxy resin is 8,000.
[0143] A covering film comprising the above resin composition, the preparation method is as follows:
[0144] Using a three-mouth glass reactor, firstly, the carboxyl-terminated butyl rubber CTBN and EBA-23 bisphenol A epoxy resin were grafted at 150°C for 30 minutes to obtain a modified epoxy resin. Then, the modified epoxy resin was mixed with bisphenol A epoxy resin NPEL-134, phenolic resin PF-2123, anhydride curing agent HN-7000, accelerator DMP-30, flame retardant OP-935 and coupling agent Z-6040 with ethyl acetate, and dispersed for 30 minutes using a sand mill with a high shear stirring and dispersing device to prepare a resin glue with a solid content of 45%.
[0145] The resin glue solution is coated onto the insulating substrate polyimide film using a coating device.
[0146] Then, the insulating substrate coated with the resin composition glue solution was heated at 120° C. for 5 minutes in an online drying oven to remove the organic solvent, thereby obtaining an insulating adhesive film of a semi-cured resin layer. The thickness of the adhesive film after drying was controlled to be 60 μm.
[0147] Examples 2 to 3
[0148] The preparation method is the same as that of Example 1, except for the raw material components, which are listed in Table 1.
[0149] Comparative Examples 1 to 4
[0150] The preparation method is the same as that of Example 1, except for the raw material components, which are listed in Table 1.
[0151] Table 1
[0152]
[0153] Performance Testing
[0154] The properties of the covering films prepared in the embodiment and the comparative example were compared, and the specific method is as follows:
[0155] (1) Initial adhesion: Determine the initial adhesion by comparing the test results using the rolling ball method.
[0156] (2) Release force: Prepare a test strip with a length of 175 mm and a width of 25 mm. The cut should be clean and straight. Use a roller to roll the sample back and forth twice at a speed of about 10 mm / s to make at least 5 samples. Use a tensile machine to stretch the test tape at an angle of 180 degrees. The data displayed on the tensile machine computer is the release force of the test piece (g / 2.5 cm). Take the average of the 5 values as the test result.
[0157] (3) Coverability: Roll the cover film and copper wire together and observe whether there are bubbles between the copper wires. If there are bubbles, the coating fails; if there are no bubbles, the coating passes. The rolling temperature is 180°C, the line speed is 5m / min, and the pressure is 12MPa; the copper thickness of the wire bundle is 100μm, the line width is 700μm, and the line spacing is 2mm.
[0158] (4) Peel strength: After the cover film and the smooth surface of 100 μm flat copper wire were rolled together, they were cured at 180°C for 160 seconds and tested according to IPCTM6502.4.9 method. The rolling temperature was 180°C, the line speed was 5 m / min, and the pressure was 0.5 MPa. The flat plate holding temperature was 180°C, the pressure was 12 MPa, and the time was 160 seconds.
[0159] (5) Glue overflow: Test according to IPCTM650-2.3.17.1 method and measure the annular spacing of glue overflow along the circumference of the punching hole on the specimen.
[0160] (6) Heat resistance test: After the cover film and the 100 μm copper foil smooth surface are rolled together, they are cured at 180°C for 160 seconds. The rolling temperature is 180°C, the line speed is 5 m / min, the pressure is 0.5 MPa, and the flat plate holding temperature is 180°C, the pressure is 12 MPa, and the time is 160 seconds.
[0161] The cured samples were cut into 5cm×5cm pieces, immersed in a 288℃ tin furnace for 5 minutes, and then taken out to observe whether there were delamination bubbles. The highest test temperature without delamination bubbles was taken as the heat resistance.
[0162] (7) Chemical resistance: After the cover film and the 100 μm copper foil smooth surface are rolled together, they are cured at 180°C for 160 seconds. The rolling temperature is 180°C, the line speed is 5 m / min, the pressure is 0.5 MPa, the flat plate holding temperature is 180°C, the pressure is 12 MPa, and the time is 160 seconds. Test according to IPCTM650-2.3.2A method.
[0163] (8) Flame retardancy: measured according to UL standards.
[0164] The performance test results are shown in Table 2.
[0165] Table 2
[0166]
[0167] For the covering film prepared by the resin composition of Comparative Example 1, increasing the proportion of CTBN leads to decreased adhesiveness, while a higher proportion of CTBN leads to increased release force, affecting separation performance and increased glue overflow, affecting the uniformity of the coating. Although CTBN contributes to flexibility, too high a proportion will affect the final peel strength. A higher CTBN proportion also affects heat resistance. Related to the amount of glue overflow, the overall covering effect deteriorates. Higher CTBN leads to decreased chemical resistance.
[0168] The cover film prepared from the resin composition of Comparative Example 2 lacks CTBN, resulting in decreased adhesiveness. Due to decreased bonding performance, the release force increases, affecting the separation performance, increasing the amount of glue overflow, and significantly decreasing the peel strength. The lack of high-quality epoxy resin and modified epoxy resin results in insufficient heat resistance.
[0169] The performance of Examples 1, 2 and 3 is better than that of Comparative Examples 1 and 2, especially in key properties such as initial adhesiveness, release force, peel strength and heat resistance. This shows that the optimized resin combination formula can effectively improve the overall performance of the material and meet the needs of new energy power battery packs and automotive high-voltage thick film flexible wiring harnesses. The significant shortcomings of Comparative Example 2 show the significant impact of raw material composition on material performance, especially the performance degradation caused by the lack of key components (CTBN and bisphenol A epoxy resin).
[0170] The samples of Example 3 were tested for their shelf life performance, and the results are shown in Table 3.
[0171] Table 3
[0172]
[0173] It can be seen from the data in Table 3 that the numerical composition provided in Example 3 of the present invention and the insulating covering film prepared therefrom, under the condition of 5°C±3°C and humidity <60%, the comprehensive performances meet the test requirements after 6 months. Starting from the 7th month, the overflow performance of the resin composition decreases, resulting in a gradual decrease in coverage, heat resistance, and chemical resistance.
[0174] The resin composition of the present invention has the characteristics of no baking and fast curing, can be directly applied to the production of covering films, can provide sufficient bonding force, and can be directly used for bonding large-diameter copper wires or thick copper foils in circuit boards. And it only takes about 160 seconds to complete hot pressing through rollers, realizing the continuous production of circuit boards. Not only does it significantly improve the storage life of the product, but it also has vital strategic significance for promoting the development of new energy power battery packs and automotive high-voltage thick film flexible wiring harnesses towards higher power, higher efficiency, lower energy consumption and lower cost.
[0175] The present invention has been described in detail above in conjunction with the embodiments, but the present invention is not limited to the above embodiments, and various changes can be made within the knowledge scope of ordinary technicians in the relevant technical field without departing from the purpose of the present invention.
Claims
1. A resin composition, characterized in that The preparation raw materials include: modified epoxy resin, epoxy resin, phenolic resin, curing agent, accelerator, flame retardant and coupling agent, and the modified epoxy resin is a rubber graft reaction polymer.
2. The resin composition according to claim 1, characterized in that In parts by weight, the raw materials for preparation include: modified epoxy resin: 100 parts, Epoxy resin: 10-20 parts, Phenolic resin: 10-20 parts, Curing agent: 5-15 parts, Accelerator: 2-10 parts, Flame retardant: 40-60 parts, Coupling agent: 0.1-0.5 parts.
3. The resin composition according to claim 1 or 2, characterized in that The preparation method of the modified epoxy resin is as follows: carrying out a grafting reaction between carboxyl-terminated butyl rubber and EBA23 epoxy resin at 150°C.
4. The resin composition according to claim 1 or 2, characterized in that The polymerization degree of the modified epoxy resin is 50% to 55%; and / or the number average molecular weight of the modified epoxy resin is 4000 to 10000.
5. The resin composition according to claim 1 or 2, characterized in that The epoxy resin is a bifunctional epoxy resin or a multifunctional epoxy resin; and / or, the epoxy value of the epoxy resin is 0.18 to 1.02 mol / 100 gr; and / or, the epoxy resin includes at least one of bisphenol A epoxy resin, bisphenol F epoxy resin, linear phenolic epoxy resin, naphthyl epoxy resin and biphenyl epoxy resin.
6. The resin composition according to claim 1 or 2, characterized in that The phenolic resin is a thermoplastic phenolic resin; and / or the curing agent includes at least one of 4,4'-diaminodiphenyl sulfone, 3,3'-diaminodiphenyl sulfone, DDS, hydrazide, methyl nadic anhydride, phthalic anhydride, tetrahydrophthalic anhydride, PN-23, PN-23J, PN-40, PN-40J and 2EMI; and / or the accelerator includes at least one of a modified amine accelerator, an imidazole accelerator, an organic urea accelerator and a hydrazide accelerator.
7. The resin composition according to claim 1 or 2, characterized in that The flame retardant includes a phosphorus-containing flame retardant; and / or the coupling agent includes a silane coupling agent.
8. A method for preparing the resin composition according to any one of claims 1 to 7, characterized in that: The method comprises the following steps: dispersing and mixing the modified epoxy resin, the epoxy resin, the phenolic resin, the curing agent, the accelerator, the flame retardant and the coupling agent in an organic solvent according to a proportion.
9. A covering film, characterized in that: The invention comprises an insulating base film and an adhesive layer coated on the insulating base film, wherein the adhesive layer is formed from the resin composition according to any one of claims 1 to 7.
10. A method for preparing the covering film according to claim 9, characterized in that: The following steps are involved: The resin composition is mixed and dispersed in an organic solvent to obtain a resin glue solution, which is then applied to the insulating base film and heated for curing.
Citation Information
Patent Citations
High temperature resistant halogen-free flame-retardant adhesive for flexible copper clad foil substrate and preparation thereof
CN101323773A
Manufacturing method of copper-clad plate and glue solution for copper-clad plate
CN101808466A
Halogen-free flame retardant epoxy resin composition and high-flexibility coating film prepared by same
CN102010569A
Epoxy resin composite and covering film prepared from same
CN102093667A
Halogen-free anti-aging epoxy resin composition and method for preparing cover film by using same
CN103694639A